(untitled) (Gestión y Gerencia, 2019)
The proposed research deduces the adaptive responses of the Venezuelan company to the governmental purpose of suppressing the market economy and affecting private property. The use of models is frequent in the microeconomic analysis, they allow to anticipate rational reactions of the productive units, due to variations in the market conditions, subject to the fulfillment of certain assumptions. The behavior of the company in the event of a possible suppression of the market, constitutes a novelty. An approach to their study is undertaken taking as a starting point the Perfect Competition model (PC), then proceeds to raise the basic assumptions, introducing restrictions that simulate real situations occurred in the third luster of the present century. The answers are predictable: adjustments in the level of production, in the composition of the range of products to be offered, the number of workers, reduction of expenses in acquisition of machinery and equipment (investment) and in technological improvements, in order to keep operative the plants and, in extreme cases, cease operations. The main finding is paradoxical: to survive, the company is doomed to be inefficient in the allocation of resources.